Prefrontal cortex: Review - Zararsiz, Ismail; Sarsilmaz, Mustafa (Turkiye Klinikleri, 2005)
The prefrontal cortex comprises a great portion of the gyri frontalis superior, frontalis medius and frontalis inferior, as well as half of the frontal gyrus cinguli. It is responsible for such cognitive functions as learning, memory, motor response planning, the recognition of written words, and the analysis of knowledge. In addition, it plays a key role in the regulation of behaviour and personality. The prefrontal association area has been shown to be an important structure for the processing of ideas. It is thought to play a role in conveying new information to the brain and in the formation of the working memory necessary for the analysis of this information. Detailed knowledge of the structure and function of the prefrontal cortex is essential for the accurate diagnosis of damages caused by lesions in this region. Copyright © 2005 by Türkiye Klinikleri.
Prefrontal korteks
Keywords: Physiology; Prefrontal cortex